Regular mailing of personalized feedback reports improves glycemic control in diabetes: A randomized controlled trial1: 定期邮寄个体化的反馈报告可以改善糖尿病患者的血糖控制:一项随机对照试验. (5th March 2017) - Yin, Junmei; Luk, Andrea; Wong, Rebecca; Chung, Harriet; Kong, Alice; Ozaki, Risa; Ma, Ronald; Chow, Chun‐Chung; So, Wingyee; Chan, Juliana
Highlights: Patients with diabetes who underwent structured complication assessment and received a personalized report through a web‐based portal showed significant improvement in glycemic and lipid control after 1 year. Under comprehensive care, those who received additional follow‐up reports had further reduction in HbA1c. In a post‐hoc analysis, patients with chronic kidney disease who received additional follow‐up reports were less likely to be hospitalized and had shorter length of stay.